Positive effect of compound amino acid chelated calcium from the shell and skirt of scallop in an ovariectomized rat model of postmenopausal osteoporosis. (27th August 2021) - Song, Jiale; Liu, Guofeng; Song, Yahui; Jiao, Kui; Wang, Shanglong; Cao, Tingfeng; Yu, Jia; Wei, Yuxi
Abstract: BACKGROUND: Osteoporosis has become an important public health issue with the increase of aging population, and afflicts millions of people worldwide, particularly elderly or postmenopausal women. In the present study, we prepared compound amino acid chelated calcium (CAA‐Ca) from processing by‐products of Chlamys farreri, and evaluated its effect on postmenopausal osteoporosis with an ovariectomized (OVX) rat model. RESULTS: A 60‐day treatment of OVX rats with CAA‐Ca significantly enhanced the bone mineral density (BMD) and the bone calcium content. Meanwhile, some bone morphometric parameters, trabecular bone number (Tb.N), trabecular bone volume fraction (BV/TV), trabecular bone thickness (Tb.Th) and cortical bone wall thickness (Ct.Th), were also increased by 8.20%, 118.18%, 32.99% and 19.10%, respectively. In addition, the alkaline phosphatase (ALP) levels in serum were significantly reduced after CAA‐Ca treatment, while the blood calcium levels were increased. Mechanistically, CAA‐Ca down‐regulated the levels of receptor activator of nuclear factor‐ κ B (RANK) and receptor activator of nuclear factor‐ κ B ligand (RANKL), and up‐regulated osteoprotegerin (OPG) levels in osteoclasts, inhibiting bone resorption and bone loss. Meanwhile, CAA‐Ca treatment raised β ‐catenin levels and lowered Dickkopf1 (DKK1) levels in the Wnt signaling pathway of osteoblasts, which can promote calcium absorption and bone formation. CONCLUSION: The results suggested that CAA‐Ca promoted bone formation, inhibited bone resorption and improved bone microstructure. Therefore, this study contributes to the potential application of CAA‐Ca as a functional food resource in the treatment of postmenopausal osteoporosis. © 2021 Society of Chemical Industry